Grammaticalité et changement d’acceptabilité : le cas de help - Mathilde Pinson (Anglophonia, 2018)
This paper aims at establishing the role of processing factors on the evolution of acceptability in two case studies: the infinitival complementation of the verb help (with or without to) and the distribution of the construction [capacity + help]. The corpora chosen for this study, in particular COHA and the Old Bailey Proceedings, reveal that these factors do not simply help to explain the low frequency of dispreferred structures, but can even be considered the main factor triggering language change, in line with Rohdenburg’s prediction (2003: 243). The principle of horror aequi (Brugmann 1909) turns out to be the initial impetus leading to the current disappearance of to after help and questions of processing are shown to have engendered the obsolescence of the [capacity + help]NPI construction. As these processing factors limit the frequency of dispreferred structures, they contribute to diminishing speakers / hearers’ familiarity with these structures, which gradually alters their acceptability judgements, and, in turn, the grammar of English.